1975
DOI: 10.1177/001872087501700411
|View full text |Cite
|
Sign up to set email alerts
|

The Transition of Experienced Pilots to a Frequency-Separated Aircraft Attitude Display

Abstract: Independent groups of eight professional pilots each were given one flight in a Link GAT-2 simulator and one flight in a Beechcraft C-45H using, respectively, the moving horizon, moving airplane, and frequency-separated attitude displays. The flight tasks performed by the subjects included recovery from unknown attitudes, disturbed attitude tracking, and completion of an area navigation course. Data collected in the C-45H aircraft demonstrated superior performance of both the frequency-separated and moving hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
2

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 9 publications
2
22
2
Order By: Relevance
“…In previous research, pilots were found to sometimes make 'roll reversal errors' (RREs) when referencing the attitude indicator (AI), which is also known as the artificial horizon (Beringer, Williges & Roscoe, 1975;Hasbrook & Rasmussen, 1973;Müller et al, 2018;Singer & Dekker, 2002). These RREs, which are roll inputs towards the opposite of the required side, are thought to be facilitated by an ambiguity of the presented bank angle on the generally used moving-horizon type AI (see, Figure 1; Roscoe, 2004;Previc & Ercoline, 1999;Wickens, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, pilots were found to sometimes make 'roll reversal errors' (RREs) when referencing the attitude indicator (AI), which is also known as the artificial horizon (Beringer, Williges & Roscoe, 1975;Hasbrook & Rasmussen, 1973;Müller et al, 2018;Singer & Dekker, 2002). These RREs, which are roll inputs towards the opposite of the required side, are thought to be facilitated by an ambiguity of the presented bank angle on the generally used moving-horizon type AI (see, Figure 1; Roscoe, 2004;Previc & Ercoline, 1999;Wickens, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that tracking was more precise, recoveries from unusual attitudes were accomplished faster, and fewer control reversals occurred with the frequency-separated display (Roscoe et al). Other investigations have also shown more precise control and fewer control reversals with the frequency-separated display over the alternatives (Beringer, Williges, & Roscoe, 1975;Roscoe, 1968;. It is important to note that in one experiment, Beringer et al (1975) reported that experienced professional pilots adapted quickly to the frequency-separated display format in both simulator and flight tests.…”
Section: Sire Multisensory Crew Stationmentioning
confidence: 93%
“…Other investigations have also shown more precise control and fewer control reversals with the frequency-separated display over the alternatives (Beringer, Williges, & Roscoe, 1975;Roscoe, 1968;. It is important to note that in one experiment, Beringer et al (1975) reported that experienced professional pilots adapted quickly to the frequency-separated display format in both simulator and flight tests. The advantages of the frequency-separated display format are reported in the literature.…”
Section: Sire Multisensory Crew Stationmentioning
confidence: 93%
“…During a bank to the left, the indicator functions initially like a moving aircraft display (aircraft rotates counter-clockwise). When the aircraft assumes a steady bank angle, both the horizon line and the aircraft symbol rotate clockwise, until the aircraft element is parallel to the true aircraft bank angle (9). Pitch is represented in a manner similar to the moving horizon display.…”
Section: The Kinalog and Frequency Separated Attitude Indicatorsmentioning
confidence: 99%